The Road from Sam’al to Asitawandawa. Contributions to the Historical Geography of the Amanus Region - Alkım, U. Bahadır (Fs Bossert, 1965)
ersch. 1966; = Belleten XXIV, 1960, 349-401; A. Introduction. B. I. Amanus in the Historical Sources of the Ancient Near East; II. Amanus and the Amanic Gates in the Classical Authors; III. The Passes of Amanus in the Classical Authors; IV. Amanus and its Passes in the Byzantine Sources; V. Amanus and its Passes in the Islamic Authors; VI. Modern Names of the Amanus. C. Arslanı Bel in the Works of Modern Travellers and Geographers. D. Relations of the Sam’al and Danuna. E. Conclusion.